Profits and Prices in Prosperity and Depression: Paton, Epstein, Mills - Kreps, Theodore J.; Paton, W. A.; Epstein, Ralph C.; Clark, Florence M.; Mills, Frederick C. (Quarterly Journal of Economics, 1937)
Journal Article Profits and Prices in Prosperity and Depression: Paton, Epstein, Mills Get access Theodore J. Kreps Theodore J. Kreps Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 51, Issue 4, August 1937, Pages 681–698, https://doi.org/10.2307/1881685 Published: 01 August 1937